2023
DOI: 10.1039/d3gc00171g
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrochemical redox method for the simultaneous recovery of spent lithium-ion battery cathodes and anodes

Abstract: With the rapid development of the electric vehicles industry, an enormous amount of spent lithium-ion batteries (LIBs) had been generated. However, the traditional electrochemical recycling method suffers from high cell...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Recently an octahedral structure [Co(EG) 6 ] 2+ was reported at l max = 534 nm, which is slightly different from the value that we observe. 57 This difference may be related to a different octahedral speciation in our system, which may combine EG and other ligands available in the DES mixture. Moreover, the blue colour was maintained in both systems when heated at 50 1C, in which the electrochemical experiments were performed, indicating that Co 2+ tetrahedral coordination remained at 50 1C.…”
Section: Resultsmentioning
confidence: 97%
“…Recently an octahedral structure [Co(EG) 6 ] 2+ was reported at l max = 534 nm, which is slightly different from the value that we observe. 57 This difference may be related to a different octahedral speciation in our system, which may combine EG and other ligands available in the DES mixture. Moreover, the blue colour was maintained in both systems when heated at 50 1C, in which the electrochemical experiments were performed, indicating that Co 2+ tetrahedral coordination remained at 50 1C.…”
Section: Resultsmentioning
confidence: 97%
“…, Cd) by efficient electrodeposition. Since the conventional electrochemical system requires a high cell potential ( E cell ) and may cause environmental problems, Kong et al 197 developed a novel electrochemical redox system for simultaneous recovery of both cathode and anode materials from spent batteries. The novel system was effective for the recovery of valuable metals from spent LIBs.…”
Section: Spent Lib Recycling By the Electrometallurgical Processmentioning
confidence: 99%
“…[22][23][24] As an adjustable and eco-friendly technique, electrochemical technologies have recently been researched. [25][26][27][28] However, different electrochemical methods for recycling LIBs have different emphases. 29 Several types of lithium battery cathode materials have been recovered by electric field-driven delithium in NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…31 Meng et al used the electrochemical reduction method to leach Li and Co by using 1.25 mol L −1 of malic acid at 8 V. 32 Recently, research has demonstrated that the spent cathode and anode materials can be recovered in a low energy consumption method through the strategy of electrochemical oxidation. 27 However, the strategy only uses a half-reaction in one electrolytic cell, while the other half-reaction produces by-products. 14,[33][34][35] The simultaneous utilization of electrochemical reactions at both the cathode and anode in one electrolytic cell is beneficial for saving chemicals and reducing energy consumption, which is of great interest to explore.…”
Section: Introductionmentioning
confidence: 99%